Coping With Negative Stereotypes Toward Older Workers: Organizational and Work-Related Outcomes - Chiesa, Rita; Zaniboni, Sara; Guglielmi, Dina; Vignoli, Michela (Frontiers in Psychology, 2019)
The current study aims to test a moderated-mediation model in which the indirect effect of the presence of negative stereotypes towards older workers in the organization on psychological engagement to work domain and attitudes toward development opportunities through identification with the company depends on the occupational self-efficacy. The survey involved 1501 Italian employees over age 50, working for a major retailer of the big distribution. In line with Social Exchange theory, the results showed that the perception of negative stereotypes towards older workers in the organization is associated with low identification with the company and in turn with psychological engagement to work domain and attitudes toward development opportunities. In addition, this relationship was found to be stronger for older workers with higher and medium levels of occupational self-efficacy. These findings suggest to organizations to discourage the dissemination of negative stereotypes toward older workers in the workplace because the perception of the lack of reciprocity may lead to older workers’ disengagement from the work domain and their loss of interest toward development opportunities.